Use of Grafted Voltage Stabilizer to Enhance Dielectric Strength of Cross-Linked Polyethylene - Dong, Wei (Polymers (Basel), 2019)
Aromatic voltage stabilizers can improve the dielectric properties of cross-linked polyethylene (XLPE); however, their poor compatibility with XLPE hinders their practical application. Improving the compatibility of aromatic voltage stabilizers with XLPE has, therefore, become a new research goal. Herein 1-(4-vinyloxy)phenylethenone (VPE) was prepared and characterized. It can be grafted onto polyethylene molecules during the cross-linking processes to promote stability of the aromatic voltage stabilizers in XLPE. Fourier transform infrared spectroscopy confirmed that VPE was successfully grafted onto XLPE, and effectively inhibited thermal migration. Thermogravimetric analysis showed that the grafted VPE/XLPE composite exhibits a better thermal stability than a VPE/PE blend composite. Evaluation of the electrical properties showed that the breakdown strength and electrical tree initiation voltage of the VPE/XLPE composite were increased by 15.5% and 39.6%, respectively, when compared to those of bare XLPE. After thermal aging, the breakdown strength and electrical tree initiation voltage of the VPE/XLPE composite were increased by 9.4% and 25.8%, respectively, in comparison to those of bare XLPE, which indicates that the grafted voltage stabilizer can effectively inhibit its migration and enhance the stability of the composite material.